Efektivitas Teknik Mind Mapping Dalam Layanan Bimbingan Kelompok Untuk Meningkatkan Kemampuan Perencanaan Karir Siswa - Julia Julia; Muslim Afandi (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This research was instigated by the low of student career planning ability at State Senior High School 1 Kubu Rokan Hilir. It aimed at knowing student career planning ability, the implementation of Mind Mapping technique on Group Guidance service, and the effectiveness of Mind Mapping technique on Group Guidance service in increasing student career planning ability at State Senior High School 1 Kubu Rokan Hilir.  Quantitative approach was used in this research, and it was an experimental research with one-group pretest-posttest design.  Questionnaire, observation, and documentation were the instruments of collecting the data.  Wilcoxon test was used to analyze the data.  The research findings showed that student career planning ability before being given Mind Mapping technique on Group Guidance service was on low category and the mean was 51.  After being given Mind Mapping technique on Group Guidance service, it increased to high category and the mean was 81.  So, it could be known that there was a difference between pretest and posttest.  It could be concluded that Mind Mapping technique on Group Guidance service was effective in increasing student career planning ability, it could be seen from the probability score of Sig. (2-tailed) 0.005 that was lower than 0.05, so Alternative hypothesis was accepted.